1999
DOI: 10.1139/b99-033
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and cytochemical study of colonization of xylem vessel elements of susceptible and resistant Dianthus caryophyllus by Fusarium oxysporum f.sp. dianthi

Abstract: The colonization processes of the xylem in the susceptible carnation cv. Early Sam and the resistant cv. Novada were studied ultrastructurally following inoculation with Fusarium oxysporum f.sp. dianthi. Samples from 1 to 3 cm above the incision were collected over 5 weeks and processed following conventional procedures as well as with probes for cellulose, N-acetyl-glucosamine, and pectin. The fungus grew profusely in the vessel lumina of the susceptible cultivar. Some of the colonized vessels were lined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
83
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(98 citation statements)
references
References 26 publications
15
83
0
Order By: Relevance
“…The occurrence of fungal cell wall modifications, including desquamation, in other wilt-causing fungi, has been described and reported previously (Nicole et al 1994;Ouellette and Baayen 2000;Ouellette et al 1999aOuellette et al , 1999bOuellette et al , 2002. In this study, fungal cell wall desquamation was also observed similar to that reported for O. novo-ulmi (Ouellette et al 1999a), but in some cases, unevenness in the walls might also have been due to irregular wall formation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The occurrence of fungal cell wall modifications, including desquamation, in other wilt-causing fungi, has been described and reported previously (Nicole et al 1994;Ouellette and Baayen 2000;Ouellette et al 1999aOuellette et al , 1999bOuellette et al , 2002. In this study, fungal cell wall desquamation was also observed similar to that reported for O. novo-ulmi (Ouellette et al 1999a), but in some cases, unevenness in the walls might also have been due to irregular wall formation.…”
Section: Discussionsupporting
confidence: 89%
“…Similar structures often pervaded fungal walls and extracellular matter, and then seemed to stretch freely over void spaces or into the host cell walls. A similar association was equally observed in other fungal wilt pathogens (Nicole et al 1994;Ouellette et al 1995Ouellette et al , 1999bOuellette et al , 2002.…”
Section: Discussionsupporting
confidence: 75%
“…These were characterized by three demarcated layers: a shredded one, unlabelled for cellulose, a more compact and opaque cellulose-labelled layer, and the unlabelled VWLM layer. This type of alteration mirrored that of pit membranes of half-bordered pits in the metaxylem in DED affected elms and Fusariuminfected carnations (Ouellette 1978a(Ouellette , 1978bOuellette et al 1999Ouellette et al , 2004bOuellette et al , 2004cOuellette and Rioux 1993) and often of intertracheary pit membranes in staghorn sumac (Ouellette et al 2005a). In all instances, the term "swelling of pit membranes" should not apply, in our opinion, when it is primarily attributed to covering layers of extraneous matter, likely of a pathogen origin in most cases.…”
Section: Discussionmentioning
confidence: 81%
“…We have already described particular modes of pathogen development, of tissue alterations, of host cell reactions and related aspects concerning Dutch elm disease and Fusarium wilts of carnation, tomato and staghorn sumac (Charest et al 2004;Ouellette 1978b;Ouellette et al 1995Ouellette et al , 1999Ouellette et al , 2004aOuellette et al , 2004bOuellette et al , 2004cOuellette et al , 2004dOuellette et al , 2004e, 2005aOuellette et al , 2005b. These works present peculiar characteristics of pathogen structures, of host cell wall and content alterations related to extensive tissue invasion by opaque matter, not ascribable to a host origin, of various host cell reactions and so on, and more than circumstantial evidence was presented to show that most of the material lining vessel walls did not always correspond to the notions of coating as supported by others.…”
Section: Introductionmentioning
confidence: 99%
“…Van Dyke and Mims 1991). Opaque material associated with host wall altĂ©rations was likewise observed in plants affected with wilt diseases : elm trees with Dutch elm disease (Nicole et al 1994;Ouellette 1978;Ouellette andRioux 1992, 1993); susceptible Ft/sar/um-infected carnation plants (Ouellette and Baayen 2000;Ouellette et al 1999a);…”
Section: Discussionmentioning
confidence: 95%